162k views
5 votes
(−8k+1)(−8k+1) standard form

User Gletscher
by
4.4k points

2 Answers

4 votes

Answer:

64k² - 16k + 1

Explanation:

(−8k+1)(−8k+1)

64k² - 8k - 8k + 1

64k² - 16k + 1

User Jpoppe
by
5.1k points
1 vote

Answer:

64k^2 - 16k +1

Explanation:

We can rewrite this as

(-8k+1) ^2

We know that (a+b)^2 = a^2 +2ab +b^2

Let a = -8k and b = 1

(-8k+1) = (-8k)^2 +2*(-8k)(1) + 1^2

=64k^2 - 16k +1

User Skaeff
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.